Communication Strategy for Nagari Government Apparatus in Resolving Management Problems in the Rabaa Nagari Padang Tarok Feed Market, Baso District, Agam Regency, Indonesia - Sabri; Eka Febrianti; Asnah; Nasfi (PT. Gudang Pustaka Cendekia, 2024)
This research aims to examine the communication strategies of nagari government officials in resolving nagari market management problems in Agam Regency. Agam Regency has many traditional markets spread across several regions. One of them is Rabaa Market which is located in Nagari Padang Tarok District. Baso, Agam Regency. The market is located on the side of the road connecting Bukittinggi-Payakumbuh-Pekan Baru. There are various problems, including administrative problems regarding ownership of the market land, and there is a tug-of-war regarding land ownership status between the local community and the Agam Regency Government, which in this case is the Nagari Padang Tarok Government, which becomes an obstacle in developing market management. The method used in this research is the Osgood and Wilbur Schramm communication model and the Swot Analysis method. The problem of asset ownership status and the status of Pakan Rabaa Nagari Padang Tarok is still unresolved and still triggers disputes . The results of this research found that the communication strategy used was the Osgood and Wilbur Schramm model of communication approach , which was very effective in resolving Nagari market disputes.